The Effect of Enterprise Risk Management, Return on Assets, and Firm Size on Firm Value in Indonesian Automotive Companies - Muhammad Rafly Aprilyo; Nastiti Rizky Shiyammurti (AIBPM Publisher, 2026)
Firm value remains an important concern for Indonesian automotive companies because the sector faced post-pandemic recovery pressures, market uncertainty, and increasing investment demands during the 2020–2024 period. This study aims to examine the effects of Enterprise Risk Management (ERM), Return on Assets (ROA), and firm size on firm value in automotive companies listed on the Indonesia Stock Exchange (IDX). A quantitative approach was applied using panel data from 11 companies, resulting in 55 firm-year observations selected through purposive sampling. Firm value was measured by Price-to-Book Value (PBV), ERM by a COSO-based disclosure index, ROA by net income divided by total assets, and firm size by the natural logarithm of total assets. The data were analyzed using panel regression with the Random Effect Model (REM). The results show that ERM, ROA, and firm size simultaneously affect firm value (F = 3.3949; p = 0.0247). Partially, only ROA has a significant positive effect on firm value (b = 14.8417; p = 0.0034), while ERM and firm size have no significant effects. These findings imply that managers should prioritize profitability enhancement while strengthening the strategic integration of risk management and resource utilization to support long-term firm value creation.